BLENDED LEARNING: A 21ST CENTURY LEARNING MODEL AT COLLEGE - OSKAH DAKHI; JALIUS JAMA; DEDY IRFAN; AMBIYAR; ISHAK (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The rapid advancement of information and communication technology in the 21st century is forcing teachers who teach students at every level of education to change their behavior and mindset, even committees that support them to achieve their teaching goals. The right approach is how one can integrate technology and education, i.e., through the Blended Learning Model. This model combines the usual online teaching and teaching classrooms. The strength of this model is that it can increase interaction between students anytime and anywhere. Rapidly growing technology integration has brought powerful changes to the education system and improved digital skills for students and lecturers. Technology can also influence how think, learn, and interact. Technological developments encourage educators to understand and utilize technology in learning and learning activities to create a dynamic learning environment.